HIGH SCHOOL TEACHERS’ PERCEPTION AND ATTITUDE TOWARDS WORLD ENGLISHES: STUDY CASES IN LHOKSEUMAWE CITY, INDONESIA - Hanif Hanif; Kurniawati Kurniawati; Dini Rizki; Dewi Kumala Sari (Getsempena English Education Journal, 2025)
ABSTRACT This research explores the perceptions, attitudes, and teaching practices of senior high school English teachers in Lhokseumawe City, Aceh, Indonesia, regarding the concept of World Englishes (WE). As English continues to evolve as a global language, its use across diverse sociocultural contexts challenges traditional native-speaker norms—especially those based on British and American English. Despite this global shift, English education in Indonesia remains strongly influenced by native-speaker standards embedded within the national curriculum. Using a qualitative case study approach, the data were collected through semi-structured interviews, document analysis, and a literature review involving five English teachers from different schools in the area. The results indicate that although teachers recognize the existence of various English varieties, their comprehension of the theoretical and pedagogical principles underlying World Englishes is still limited. Most teachers continue to rely on inner circle varieties especially American and British English as the dominant teaching models, citing factors such as curriculum restrictions, insufficient exposure to global English varieties, and students’ relatively low proficiency levels. Consequently, the practical application of World Englishes in classroom instruction remains minimal. The study suggests that targeted professional development programs are essential to strengthen teachers’ sociolinguistic awareness and pedagogical skills in addressing English variation. Gradually incorporating non-native English varieties into classroom materials could foster more inclusive, realistic, and globally oriented English teaching practices in Indonesia. Keywords: World Englishes, teachers’ perceptions, English language teaching, pedagogical practice